The role of motivation in literacy assessment: using item-level analyses to inform college placement for multilingual learners - Kaldes, Gal; Braasch, Jason L. G.; Kessler, Erica (Frontiers in Education, 2025)
PurposeCollege placement assessments often overlook multilingual learners’ full linguistic abilities and literacy engagement, as standardized tests primarily assess English proficiency rather than how students interact with academic texts. Directed Self-Placement (DSP) offers an alternative approach through self-assessment, with some models incorporating post-task self-ratings of students’ competence beliefs. However, this approach does not fully capture how motivation (i.e., competence beliefs and task value) interacts with varying literacy skills within a task. This exploratory study applies Explanatory Item Response Models (EIRMs) to examine how self-rated motivation relates to vocabulary performance on higher-and lower-frequency words, offering insights to refine DSP frameworks for multilingual learners.MethodA total of 39 multilingual learners and 249 monolingual English-speaking college students completed a vocabulary assessment and responded to self-report motivation scale questions assessing their reading motivation. Item-level analyses were implemented to examine the interaction between motivation and multilingual learner status on higher-and lower-frequency words.ResultsLower-frequency words posed greater challenges across all participants but disproportionately undermined the performance of multilingual learners with lower reading competence beliefs. However, multilingual learners with higher reading competence performed comparably to monolingual English speakers on both higher and lower frequency words.ConclusionEIRM-based analyses offer novel insights into the ways that motivation interacts with different dimensions of literacy performance at the item level. Future research should develop validated self-assessment tools that incorporate additional aspects of motivation and multilingual learners’ linguistic strategies, which could inform more equitable placement practices.